Analysis of College Student Technology Literacy and Information Literacy Skills: E-Learning Activities Based on Online Platforms in Higher Education - Setyoko Setyoko; Ahmad Fauzi Syahputra Yani; Dini Fitria; Suryanti Suryanti (Postgraduate, University of Mataram, 2023)
Online platform-based e-learning makes use of a variety of technologies as communication and information mediums, encouraging students to engage in productive and worthwhile learning activitiesThis study intends to ascertain the abilities and impact of students' technological and informational literacy on their participation in online learning activities for e-learning. A descriptive quantitative research methodology is used here. Universitas Samudra and Universitas Islam Riau were the sites of the research, which took place from June to August of 2023. Students in the 155-student sample population of the Biology Education Study Program. Using google forms, interviews, and observations, a random sampling technique is used. Validation and reliability tests were conducted on the research instrument. The use of technological devices to obtain information falls into the very good category; locating available technological devices and using technological devices fall into the good category; while the use of technological devices for self-development falls into the moderate category, according to research on technological literacy skills. Information literacy among students in higher education is significantly influenced by technical literacy abilities, with an influence of 63.6%, according to the significance value (sig) 0.00 < (Î±) 0.05, which means that Ho is rejected and Ha is approved. According to the regression equation Y = 0.237 + 0.922X, the value of information literacy abilities will rise with each increase in the value of technology literacy skills. the significance of improving students' technology and information literacy skills in higher education to prepare them for the era of the digital revolution